Pelatihan keterampilan kader Posbindu PTM pada skrining awal diabetes melitus di Padukuhan Bibis, Timbulharjo, Bantul - Rohman, Fahrurie Nur; Urfiyya, Qarriy ‘Aina (INDRA: Jurnal Pengabdian kepada Masyarakat, 2026)
Diabetes Mellitus remains a major global health issue, including in Indonesia, and in one of the districts of Yogyakarta, namely Bantul. According to the top 10 disease data from the Bantul District Health Office, the number of Diabetes Mellitus (DM) cases in the Bantul area continues to increase. According to the coordinator of the Non-Communicable Disease (NCD) Posbindu (Integrated Health Post) cadre, training on diabetes mellitus screening has never been conducted, which means it does not yet support Posbindu NCD activities in identifying diabetes cases. This community service aims to improve the knowledge and skills of Posbindu NCD cadres in conducting Diabetes Mellitus screening as an effort for early detection and prevention. The community service activity involved direct demonstration-based screening training. Posbindu cadres received materials on how to perform blood sugar level tests to determine DM status, blood pressure measurement, waist circumference measurement, and body mass index (BMI) assessment. The training was attended by 8 Posbindu NCD cadres in Bibis Village on June 24, 2024. The series of activities began with a pre-test, followed by diabetes mellitus screening training, and concluded with a post-test. The results of the activity showed an increase in the knowledge and skills of Posbindu NCD cadres in conducting diabetes mellitus screening.